Emlékezés Visky Károlyra (1908-1984), a római jog nemzetközi hírű művelőjére - Hamza, Gábor (Gerundium, 2016)
KÁROLY VISKY WAS AN INTERNATIONALLY KNOWN SCHOLAR OF ROMAN LAW. he present paper describes the life and scholarly activities of Dr. Károly Visky, who was a sub auspiciis scholar of law at the Royal István Tisza University of Debrecen. he paper highlights the fact that Visky achieved a highly respectable scholarly career while working as a practising lawyer. He did not hold an academic chair, yet he became an internationally recognized representative of the study of Roman law in Hungary. he paper introduces the main ideas of his most important scholarly writings.